Factor structure of the Cannabis Experiences Questionnaire in a first‐episode psychosis sample. Issue 3 (20th October 2017) - Birnbaum, Michael L.; Cleary, Sean D.; Ramsay Wan, Claire; Pauselli, Luca; Compton, Michael T.
Abstract : Aim: The Cannabis Experiences Questionnaire (CEQ) was developed to measure the subjective experiences of cannabis use both during and after intoxication. Despite the need to better understand the nature of the complex and significant relationship between cannabis use and early psychosis, this questionnaire has rarely been used in individuals with first‐episode psychosis. Methods: We conducted a set of factor analyses using CEQ data from 194 first‐episode psychosis patients who used cannabis in order to uncover the underlying factor structure of the questionnaire and thus the overarching types of psychological experiences during/after using cannabis in young people with psychotic disorders. Results: Our exploratory factor analysis identified 4 subscales, including: Distortions of Reality and Self‐Perception (Factor 1), Euphoria Effects (Factor 2), Slowing and Amotivational Effects (Factor 3), and Anxiety and Paranoia Effects (Factor 4). Conclusions: Elucidating the underlying factor structure of the CEQ in first‐episode psychosis samples could help researchers move towards a deeper understanding of the types of experiences associated with cannabis intoxication among young adults with first‐episode psychosis and could inform the development of programs designed to reduce use, improve the course of illness, and possibly delay or prevent the onset of psychotic symptoms in those at risk.